Preparation and Characterization of PMMA-AgNPs Polymer Composite as a Dental Prosthesis - Bendjama, Adel; Abu Bakar, Mohd Fadzelly; Sabran, Siti Fatimah; Durumin Iya, Sani Garba (Asian Journal of Chemistry, 2020)
Silver nanoparticles (AgNPs) have been used for centuries in the field of medicine due to the antimicrobial properties. AgNPs has been synthesized and incorporated in different aspects of biomaterials. It is reported that AgNPs as a result of its small size, it provides sufficient antimicrobial effect at lower filler level, thus can be used in dentistry for prevention and reduction of biofilm formation on a surfaces of dental prosthesis. The purpose of this study is to develop AgNPs antimicrobial acrylic resin for dental prosthesis. The effect of AgNPs incorporated into acrylic resin poly methyl methacrylate (PMMA) on the bacterial biofilm was studied in terms of bacterial growth and the incorporating effect on the thermal stability of these polymeric biocides was evaluated. Silver nanoparticles in colloidal form was added to PMMA(ONDA-CRYL) using microwave and make four dental prosthesis at the different concentration. The specimens were delivered to the four toothless patients for 21 days. The formed biofilm was tested for microbiological study (taxonomic profile). After setting, the specimens were characterized to determine the spatial distribution of AgNPs on the PMMA matrix through scanning electron microscope and the thermal stability was examined using TGA and DSC. The modified PMMA prosthesis base containing AgNPs, which exhibited good in vivo antimicrobial properties without altering their thermal properties of degradation as well as their mechanical properties and minimize the maximum infectious signs by reducing the formation of microbial biofilm forming on the surfaces of dental prostheses. As the modification of PMMA with AgNPs improved the anti-biofilm properties without altering its mechanical and thermals properties to the degradation, it could be used as a dental prosthesis.